2012
DOI: 10.3354/meps09946
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient addition increases consumption rates of tropical algae with different initial palatabilities

Abstract: While nutrient enrichment increases herbivory rates on highly palatable species of tropical algae, it is unclear how nutrient enrichment affects species with differing initial palatabilities. We determined that there was a wide range in relative palatability among 5 perennial and common species of Caribbean coral reef algae in a cafeteria-style choice experiment, with overall preference for Acanthophora spicifera the highest, Dictyota dichotoma and Caulerpa sertularioides intermediate, and Turbinaria turbinata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In this study we investigated (1) whether herbivorous fishes preferentially fed on Sargassum polycystum fronds collected from areas with few herbivorous fishes versus areas with many, (2) whether the difference in palatability we observed could result from an induced response to fish grazing, and (3) whether differential tissue toughness or nutritional value were associated with feeding preference, as has been demonstrated in some studies of insects, marine invertebrates, or fishes (Littler & Littler 1980, Coley 1983, Burkepile & Hay 2009, Chan et al 2012). …”
Section: Introductionmentioning
confidence: 91%
“…In this study we investigated (1) whether herbivorous fishes preferentially fed on Sargassum polycystum fronds collected from areas with few herbivorous fishes versus areas with many, (2) whether the difference in palatability we observed could result from an induced response to fish grazing, and (3) whether differential tissue toughness or nutritional value were associated with feeding preference, as has been demonstrated in some studies of insects, marine invertebrates, or fishes (Littler & Littler 1980, Coley 1983, Burkepile & Hay 2009, Chan et al 2012). …”
Section: Introductionmentioning
confidence: 91%
“…Nitrogen concentration is another important factor that affects the palatability of brown algae [13]. Nutrient enrichment is known to result in increased palatability [14], decreased phlorotannin concentration [11], and increased nitrogen concentration [15]. However, it is unclear whether decreased phlorotannin concentration or increased nitrogen concentration is responsible for increased palatability caused by nutrient enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…Selective removal of enriched resources has been documented in numerous studies (e.g., Boyer et al 2004;Chan et al 2012; but to this point it has remained unclear whether N versus P drives this pattern. We found that N-enriched algae is preferentially consumed by parrotfishes but that P-enrichment had little effect on parrotfish foraging.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, animals are often N and P-limited and selectively forage on resources rich in these nutrients (Mattson 1980;; Lemoine et al 2013). Indeed, experiments comparing the consumption of nutrient enriched algae to controls often document higher rates of grazing and biomass removal of algae enriched with N and P (e.g., Boyer et al 2004;Chan et al 2012). However, as of yet no studies have differentiated the effects of N versus P on reef fish foraging, nor clarified the responses of different fish taxa to these enrichments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation